STUDI SPILLOVER EFEK EXCHANGE-TRADED FUNDS (ETFs) DI ASEAN - Juliana, Ahmad; Mutoharo, Apriliani (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
The volatility of financial security make an investor difficult and inaccurate to predict the value of targeted investation. The failure for predicting the value of financial asset will mitigate for either succeed or not an investation. That condition will not happen if an investor has knowledge for predicting the volatility financial asset. There for, we need study for forecasting the spillover effect of financial asset using ARCH-GARCH model. The novelty of this study is, we compare the three of ASEAN ETFs that still rarely investigate, are: Indonesia, Malaysia and Singapore using 5 samples of ETFs. We applied Autoregressive Conditional Heteroskedasticity (ARCH) and Generalized Autoregressive Conditional Heteroskedasticity (GARCH) for predicting the spillover efect. The result of unit root test shown that the data not stationer at level, however stationer at first difference. The result of GARCH for JK-LQ45, EWS and EIDO are not significant and it mean there is not ARCH effect. In contract the result are significant for ETF EWM and FXSG. We also found the best AIC are from ETF EWS and ETF FXSG.